(untitled) (Damascus University Journal of Historical Studies, 2023)
Under the dark circumstances which Europe had lived in the ear studied research lightened by Cordoba and its Mosque which was as a perfect scientific university and one of the largest and a famous universities in the world. The students who entered this universities were thousands and the majority study Alfigeh and lawyering and mental scientists , the graduator of this university was a famous one not only in Andalus but also in all the world. The Islam could with its intellectual heritage scientific shining and cultural helped the Europeans to go out ignorance to science from weakness to strength, wilderness to urbanize and backwardness to civilized from the darkness of life to its lighting.